PENGARUH NAUNGAN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG DAUN (Allium fistulosum L.) DI BANDUNGAN, JAWA TENGAH - Ismi Alfii Anni; Endang Saptiningsih; Sri Haryanti (Jurnal Akademika Biologi, 2013)
Onions ( Allium fistulosum L. ) is a vegetable that is often consumed by public . People often consume on the part of young leaves . Onions production decreased during the rainy season . One way to increase the growth and production of onions by adjusting the light intensity that is appropriate . Shade is one effort intensity of the sun setting to the plant . The purpose of this research was to determine the effect of shade on the growth and production of onions . The research conducted at Sidomukti Village, Bandungan and laboratory BSF, FSM, Diponegoro University. The research design using the single factor RAL: shade . Data analysis using ANOVA followed by Duncan's Multiple Range Test Test ( DMRT ) confidence level 95 % . The parameters were  plant height , number of tillers , wet weight , dry weight , chlorophyll content , stomatal number . The results showed that the difference was not significantly different shade to the number of tillers , fresh weight , chlorophyll content , and the number of stomata , but showed significantly different results to height and plant dry weight . Paranet shade with 2 coats of 10950-24850 lux light intensity and give the highest production growth in height and plant dry weight. Keyword: onions, growth, production